2009
DOI: 10.1088/0957-4484/20/21/215101
|View full text |Cite
|
Sign up to set email alerts
|

The chemical fate of the Cd/Se/Te-based quantum dot 705 in the biological system: toxicity implications

Abstract: QD705 is a cadmium/selenium/tellurium (Cd/Se/Te)-based quantum dot with good potential for biomedical applications. Although the biological fate of QD705 is established, its chemical fate in the biological system is still unknown. Since the chemical nature of Cd in QD705 (either stays as bounded Cd or becomes free Cd) is closely related to the toxicity of this nanocrystal, information on its chemical fate is critically needed. In this study we investigated the chemical fate of QD705 in the kidneys of mice. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 25 publications
6
42
0
Order By: Relevance
“…This ambiguity undermines the reliability of the ICP-AES method for the assessment of NP concentration in vivo. CdTe QD degradation in vivo and toxicity due to Cd 2+ leakage are possible and the fact was reported earlier Lin et al 2009). Consequently, lower Cd accumulation after coating the nanoparticles can be explained in two ways: a) the coating stabilizes the CdTe core and minimizes Cd 2+ release; b) the coating increases the overall NP size, which results in reduced penetration through placental barrier.…”
Section: In Vivo Studies Of Transplacental Passage Of Nanoparticlessupporting
confidence: 56%
“…This ambiguity undermines the reliability of the ICP-AES method for the assessment of NP concentration in vivo. CdTe QD degradation in vivo and toxicity due to Cd 2+ leakage are possible and the fact was reported earlier Lin et al 2009). Consequently, lower Cd accumulation after coating the nanoparticles can be explained in two ways: a) the coating stabilizes the CdTe core and minimizes Cd 2+ release; b) the coating increases the overall NP size, which results in reduced penetration through placental barrier.…”
Section: In Vivo Studies Of Transplacental Passage Of Nanoparticlessupporting
confidence: 56%
“…Thus, QD-705 is not stable or biologically inert as free Cd released from QD-705 may increase the risk of nephrotoxicity because MTs bind these metal NPs and are specifically induced to prevent nephrotoxicity. 54 …”
Section: Mts and Npsmentioning
confidence: 99%
“…[23][24][25] When QDs degrade (ie, surface atoms are lost and QDs decrease in size), blue shifts in the fluorescence-excitation spectra and decreases in the quantum yield are observed. 31 However, using fluorescence intensity to quantify QDs in tissues has been deemed to be problematic, due to the high and variable background fluorescence that results from the tissues.…”
mentioning
confidence: 99%
“…32 Furthermore, Lin et al reported that only free Cd 2+ dissociated from QDs, not QDs themselves, could induce MT production in tissues. 25 Therefore, an elevation in MT expression can be used as a good biological index of QD degradation in vivo. To reduce the effects of other metals on MT expression, CdTe QDs were selected in the present study rather than core-shell-structured CdTe/ZnS QDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation